Analisis Pengaruh Intensitas Pencahayaan terhadap Kelelahan Mata Mahasiswa Menggunakan Metode Regression Statistical Analysis dan Analisis Deskriptif - Stefani Galuh Kristanti; Dian Tiara Rezalti (Universitas Sarjanawiyata Tamansiswa, 2022)
Lack of lighting intensity levels can harm students. The most significant impact is the occurrence of eye fatigue. Eye fatigue is a condition in which the eye muscles are overused. They are forced to work hard to see objects for a long time. This study aimed to determine the effect of lighting intensity on student eye fatigue, the level of eye fatigue in students when working on assignments, and the level of student performance when working on assignments at certain lighting levels. The research data was taken at the Integrated Laboratory of the Bachelorwiyata University Tamansiswa on May 24-25, 2022. In processing the data, the method used was Regression Statistical Analysis, a statistical method used to form a model or relationship between one or more independent variables X with a response variable. Y. The results showed that the intensity of lighting affected eye fatigue in students. In session 1 the results were Y=26.62+7.49X, in session 2 the results were Y=23.96+5.47X, and in session 3 the results were Y=26.65+4.17X. Lighting also affects student performance, as indicated by the average score in session 1 is 35.50, in session 2, the average value is 55.33, and session 3 shows an average score of 47.67.